Aransas - Harrigan, Stephen, 1948- (Univ Of Texas Press, 2014)
A critically acclaimed debut novel first published in 1980, Aransas recounts a young man?s attempt to find his place in the world as he navigates the moral dilemma of training an "exquisitely conscious being" to perform in a seaside dolphin circus.